Ultra‐short‐term versus short‐term measures of heart rate variability in specialist police units: A pilot reliability study - Colin D. Tomes; Elisa F. D. Canetti; Ben Schram; Robin Orr (Physiological Reports)
Abstract Police officers are exposed to high levels of stress. Serving on Special Weapons and Tactics (SWAT) teams is a highly demanding duty that may further increase levels of stress in police personnel. This stress may accumulate, thereby increasing allostatic load. As such, holistic stress measures may be valuable for quantifying multifactorial stress accumulation in SWAT personnel. Heart rate variability (HRV) is one field‐deployable measure that may be suitable in this context. However, with logistical challenges present in this population, determining if 30 s; rather than more the typical 5‐min ECG data collection, provides sufficient reliability may be beneficial for reducing the logistical barrier to adoption of HRV monitoring in SWAT personnel. This study compared 30‐s to 5‐min HRV analyses of ECG data obtained from 15 male SWAT personnel. Findings demonstrated good (ICC >0.8) reliability only in the VLF, HF, SD1, and SD2 HRV domains. The VLF and SD2 measures may be erroneous, as 5‐min may still insufficiently characterize these measures. However, this study confirms the robust quality of nonlinear HRV analysis, as the SD1 value demonstrated the highest ICC reported here (0.902). Therefore, while 5‐min ECGs may still preferable, the 30‐s measure may still be viable for organizations considering HRV assessment.